Assessing the fish community structure in the Tubbataha Reefs Natural Park, Palawan using baited remote underwater video systems - Libatog, Chloie Mae B. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
The Tubbataha Reefs Natural Park (TRNP) is nationally-managed marine protected area (MPA), with local and international importance, that requires constant monitoring due to inevitable biophysical threats. Underwater visual census has been the standard monitoring method in the TRNP while baited remote underwater video system (BRUVS) is a new technique which uses cameras to survey fish assemblages. In this study, BRUVS were deployed across 16 stations in October 2019 and May 2021 at depths ranging from 6-16 m. Thirty-minute footages were analyzed using EventMeasure to obtain measures for diversity, abundance, and biomass, which were then evaluated across factors (i.e., year, depth, location, habitat). A total of 3,038 individuals belonging to 238 species were present in the TRNP. Mean values of 253.17 individuals (n=12) and 59.58 kg (n=11) were recorded for abundance and biomass, respectively, wherein Pomacentridae was the most abundant family while Acanthuridae had the highest biomass. Secondary consumers dominated in terms of abundance while tertiary consumers dominated in terms of biomass. Scheirer-Ray-Hare test showed that year and location, and significant interactions of year with factors such as habitat and depth were significant drivers of the patterns in fish assemblage. Significant fluctuations in years were observed, which are indicative of possible disturbance within the MPA, although this factor needs further investigation due to different stations surveyed each year. Species richness decreased in 2021 while biomass was associated with depth. Differences in locations were found among omnivores only and both habitat types exhibited similar assemblages due to the geographic landscape in the TRNP. Overall findings demonstrate the benefits of establishing MPAs in offshore reefs and how BRUVS can provide sufficient data for fish assessments that can complement UVC. It is recommended to complement the current findings with physicochemical data and benthic assemblages in the TRNP to further understand the observed patterns.